Segmental Sinusoidal Model for Speech Signal Coding - Setiawan, Florentinus Budi; Soegijoko, Soegijardjo; Sugihartono, Sugihartono; Tjondronegoro, Suhartono (UI Scholars Hub, 2006)
Segmental Sinusoidal Model for Speech Signal Coding. Periodic signal can be decomposed by sinusoidal component with Fourier series. With this characteristic, it can be modeled referring by sinusoidal form. By the sinusoidal model, signal can be quantized in order to encode the speech signal at the lower rate. The recent sinusoidal method is implemented in speech coding. By using this method, a block of the speech signal with 20 ms to 30 ms width is coded based on Fourier series coefficients. The new method proposed is quantization and reconstruction of speech signal by the segmental sinusoidal model. A segment is defined as a block of the speech signal from certain peak to consecutive peak. The length of the segment is variable, instead of the fixed block like the recent sinusoidal method. Coder consists of the encoder and the decoder. Encoder works to code speech signal at variable rate. Then coded signal will be transmitted to receiver. On the receiver, coded signal will be reconstructed, so that the reconstruction signal has the near quality compared with the original signal. The experimental results show that the average of segmental SNR is more than 20 dB.